Bari Culture: An Integrated-Collaborative Learning Strategy of Writing Exposition Text - Masayu Gay; Idrus Ahmad; Julia Ismail (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2020)
This article gives an explanation of the concept of integrative-collaborative culture of new cultures as a strategy in Indonesian Language Learning (PBI). The aim is to provide a perspective on the importance of innovation in learning. This article was written using a descriptive analytical approach. The strategy of writing an integrative-collaborative exposition text of the new culture is applied with syntax, namely 1) apperception, 2) conceptual explanation, 3) forming groups, 4) gathering information, 5) processing information, 6) communicating, and 7) reflection. Assessments are carried out through portfolios and observations, while gradations that can be assessed include attitudes, knowledge, and skills. In the process, the teacher must assist each group intensively.